Preparation method and application of oxidized sodium alginate

By using sodium periodate oxidation and ethylene glycol in the preparation process of oxidation of sodium alginate, combined with multiple filtration and hydrolysis steps, the problem of unstable oxidation degree is solved, and the stable oxidation degree and controllable degradation rate of sodium oxidation of sodium alginate is achieved. It is suitable for drug-loaded microspheres, tissue engineering stents and in vivo wound dressings.

CN119798480AActive Publication Date: 2025-04-11QINGDAO BRIGHT MOON SEAWEED GROUP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510166483.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-22
Filing Date
2025-02-14
Publication Date
2025-04-11
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

The oxidation degree of sodium oxidized alginate is unstable, which affects its gel performance and degradation rate in practical applications.

Method used

Sodium alginate is oxidized by sodium periodate to form aldehyde groups, and then oxidation reaction is terminated using ethylene glycol. The oxidation degree is controlled through multiple filtration and hydrolysis steps to protect the aldehyde group and ensure the stability of the oxidation degree.

Benefits of technology

The oxidation stability of sodium oxidized alginate is achieved, ensuring that its degradation rate is controllable in applications such as drug-loaded microspheres, tissue engineering stents and in vivo wound dressings, and meet specific needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005272608550000061
    Figure BDA0005272608550000061
  • Figure BDA0005272608550000071
    Figure BDA0005272608550000071
Patent Text Reader

Abstract

The invention relates to the technical field of bioengineering, and particularly discloses a preparation method and application of oxidized sodium alginate. The invention relates to a preparation method and application of oxidized sodium alginate. Precipitating: adding excessive acetone into the reacted solution, centrifugally dewatering, precipitating, separating and drying to obtain powder A; condensation: uniformly mixing the powder A with ethylene glycol, introducing dry HCl gas, carrying out heat preservation at 14-16 DEG C for 6-7 hours, extracting with chloroform, drying an extract, and evaporating the chloroform to obtain powder B; filtering is performed; hydrolysis: adding water to dissolve the powder C, adding phosphoric acid to adjust the pH value, reacting for 1-1.2 hours, adding excessive acetone, standing, precipitating, separating and drying, and repeating the processes of adding acetone, precipitating, separating and drying for many times to finally prepare oxidized sodium alginate powder; the preparation method provided by the invention has the advantage that the oxidation degree of the oxidized sodium alginate is more stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of bioengineering technology, and more specifically, to a preparation method and application of oxidized sodium alginate. Background Art

[0002] Sodium alginate is a type of polysaccharide extracted from brown algae. Sodium alginate has gel properties. Adding divalent cations such as Ca to the sodium alginate solution 2+ , Ba 2+ , Sr 2+ These cations interact electrostatically with the carboxyl groups on the guluronic acid of alginate to form a milky white gel. Sodium alginate also has high biocompatibility and no degradation enzymes in the body.

[0003] Due to its biocompatibility, low toxicity and relatively low price, alginate is widely used in drug release systems and tissue engineering. However, there is no degrading enzyme in the human body, and the degradation rate of alginate itself is very low. Compared with the original alginate hydrogel, the strength of oxidized alginate hydrogel shows a significant downward trend over time. In practical applications, it is necessary to select an appropriate oxidation degree that combines its degradation time and gel performance.

[0004] After sodium alginate is oxidized to obtain oxidized sodium alginate, the oxidized sodium alginate needs to be purified. Since the aldehyde group is relatively active, the aldehyde group may be affected by the purification operation or the environment during the purification process, causing the aldehyde group to react and affect the final oxidation degree of the oxidized sodium alginate. Since the influence of the aldehyde group is uncontrollable, it is difficult to predict the performance of the final product of the oxidized sodium alginate, resulting in an unstable oxidation degree of the obtained oxidized sodium alginate, which does not meet the initial expectations. Summary of the invention

[0005] In order to make the oxidation degree of oxidized sodium alginate more stable, the present application provides a preparation method and application of oxidized sodium alginate.

[0006] In a first aspect, the present application provides a method for preparing oxidized sodium alginate, using the following technical solution: A method for preparing oxidized sodium alginate comprises the following steps: Oxidation: Add sodium alginate into water to prepare sodium alginate solution, add sodium periodate solution into the sodium alginate solution and mix well, react at 50-70°C for 2-2.2h, then add excess ethylene glycol to terminate the oxidation reaction; Precipitation: add excess acetone to the solution after the reaction, centrifuge, dehydrate, precipitate, separate and dry to obtain powder A; condensation: after powder A and ethylene glycol are evenly mixed, dry HCl gas is introduced, and after keeping warm at 14-16°C for 6-7 hours, chloroform is used for extraction. After the extract is dried, the chloroform is evaporated to obtain powder B; Filtration: Powder B is dissolved in acetone, and magnetic stirring is performed to form a uniform solution. The uniform solution is filtered multiple times using a filter membrane to obtain a filtrate. The filtrate is subjected to static precipitation, separation, and drying to obtain powder C; Hydrolysis: After powder C is dissolved in water, phosphoric acid is added to adjust the pH. After reacting for 1-1.2 hours, excess acetone is added, and static precipitation, separation, and drying are performed. The process of adding acetone, precipitation, separation, and drying is repeated many times to finally obtain oxidized sodium alginate powder.

[0007] By adopting the above technical scheme, under the action of sodium periodate, the carbon-carbon bond in the cis-diol structure of sodium alginate is broken to form two aldehyde groups, the oxidation process of sodium alginate is completed, and oxidized sodium alginate is obtained, and excess ethylene glycol is used to terminate the oxidation reaction, the oxidation degree of the oxidized sodium alginate is controlled within a desired range, and acetone is used for crude extraction, and the oxidized sodium alginate and impurities such as miscellaneous proteins are precipitated; The aldehyde group of oxidized sodium alginate reacts with ethylene glycol to form acetal. The chemical properties of acetal are relatively stable. It is not easy to denature and react in subsequent repeated precipitation, centrifugation and filtration operations. Through multiple filtrations, the content of impurity proteins in the filtrate can be effectively reduced. After adjusting the pH with phosphoric acid, the hydrolysis reaction of acetal is promoted, the protection of aldehyde group is released, and acetone is used for precipitation. The ethylene glycol generated by the hydrolysis reaction and the phosphoric acid used as a catalyst are dissolved in acetone, while the oxidized sodium alginate has a low solubility in acetone and precipitates, thereby preparing oxidized sodium alginate with higher purity. At the same time, the aldehyde group in the oxidized sodium alginate is protected during the purification process, so that the oxidation degree of the finished product oxidized sodium alginate is relatively stable and can meet the requirements of a specific oxidation degree.

[0008] Preferably, in the sodium alginate solution, the concentration of sodium alginate is 8-10wt%, and the molar ratio of sodium alginate to sodium periodate is 1:0.03-0.04.

[0009] By adopting the above technical solution and controlling the molar ratio of sodium alginate to sodium periodate, the degree of oxidation of sodium alginate by sodium periodate can be effectively controlled, thereby controlling the oxidation degree of oxidized sodium alginate.

[0010] Preferably, the molar ratio of the powder A to ethylene glycol is 1:0.01-0.02.

[0011] By adopting the above technical solution and controlling the molar ratio between powder A and ethylene glycol, the aldehyde groups in the oxidized sodium alginate in powder A all undergo condensation reaction with ethylene glycol, so that the aldehyde groups are fully protected.

[0012] Preferably, in the hydrolysis step, phosphoric acid is added to adjust the pH to 3.5-4.

[0013] By adopting the above technical scheme, the pH of the solution is adjusted so that the acetal can be hydrolyzed to generate aldehyde and alcohol in an acidic environment, thereby removing the protection of ethylene glycol on the oxidized sodium alginate. Too high a pH value tends to reduce the hydrolysis rate of the acetal, while too low a pH value tends to cause precipitation of the oxidized sodium alginate.

[0014] Preferably, the filter membrane is a hydrophilically modified polytetrafluoroethylene filter membrane.

[0015] By adopting the above technical scheme, the polytetrafluoroethylene filter membrane has good resistance to organic solvents and can be used to filter acetone. The hydrophilically modified polytetrafluoroethylene filter membrane has good hydrophilicity and anti-fouling properties. The microporous structure of the filter membrane can effectively filter out impurities with large molecular weight such as foreign proteins contained in powder B, while the molecular weight of oxidized sodium alginate generated after oxidation of sodium alginate is reduced and passes through the polytetrafluoroethylene filter membrane together with acetone.

[0016] Preferably, the preparation method of the hydrophilic modified polytetrafluoroethylene filter membrane comprises the following steps: after mixing the polytetrafluoroethylene filter membrane, sodium p-styrene sulfonate, sodium bisulfite and water, heating to 55-60°C after introducing nitrogen, slowly and continuously dripping acrylic acid and ammonium persulfate, reacting for 5-5.5 hours, taking out the polytetrafluoroethylene filter membrane, washing, and drying to obtain the hydrophilic modified polytetrafluoroethylene filter membrane.

[0017] By adopting the above technical scheme, sulfonic acid groups are introduced on the surface of the polytetrafluoroethylene filter membrane by copolymerization of sodium styrene sulfonate and acrylic acid, so that the polytetrafluoroethylene filter membrane has good hydrophilicity. The impurity proteins in the oxidized sodium alginate are mostly hydrophilic proteins. After the polytetrafluoroethylene is modified, the adsorption effect on the hydrophilic proteins is increased. At the same time, more hydrophilic copolymers are deposited on the surface of the modified polytetrafluoroethylene filter membrane, which makes the polytetrafluoroethylene filter membrane not easy to adsorb proteins. The hydrophilically modified polytetrafluoroethylene filter membrane has good anti-fouling performance when in use.

[0018] Preferably, the mass ratio of sodium p-styrene sulfonate to acrylic acid is 6:(6.8-7.1), and the concentration of sodium p-styrene sulfonate is 11-12wt%.

[0019] By adopting the above technical scheme, the mass ratio and concentration of sodium p-styrene sulfonate and acrylic acid are controlled, thereby regulating the deposition amount of the hydrophilic copolymer on the surface of the polytetrafluoroethylene filter membrane, improving the hydrophilicity and making the polytetrafluoroethylene filter membrane have good anti-fouling performance.

[0020] In a second aspect, the present application provides an application of oxidized sodium alginate, using the following technical solution: An application of oxidized sodium alginate. The oxidized sodium alginate is used alone or in combination with sodium alginate to be used for drug-loaded microspheres, tissue engineering scaffolds and in vivo wound dressings.

[0021] By adopting the above technical scheme, the oxidation degree of the oxidized sodium alginate prepared by the preparation method of the present application is relatively stable, the aldehyde groups in the oxidized sodium alginate are less affected by the environment and reagents during the purification process, the oxidation degree of the prepared oxidized sodium alginate meets the initial expectations, and the oxidation degree of the oxidized sodium alginate can be relatively stably regulated, thereby regulating the degradation rate of the drug-loaded microspheres, tissue engineering scaffolds and in vivo wound dressings in the human body.

[0022] In summary, this application has the following beneficial effects: 1. Since the present application uses ethylene glycol to react with the aldehyde group in oxidized sodium alginate to generate acetal, the property of acetal is relatively stable. When the oxidized sodium alginate is subjected to purification operations such as precipitation, centrifugation and filtration, the acetal is not easily affected by the environment and reagents, and the aldehyde group in the oxidized sodium alginate is effectively protected; 2. In the present application, phosphoric acid is preferably used to adjust the pH, catalyze the hydrolysis reaction of acetal, and restore the aldehyde group of oxidized sodium alginate. Phosphoric acid and the generated ethylene glycol are dissolved in acetone. The oxidized sodium alginate has a low solubility in acetone and precipitates. After static precipitation, oxidized sodium alginate powder is obtained; 3. The oxidized sodium alginate in the present application can be used for drug-loaded microspheres, tissue engineering scaffolds and in vivo wound dressings. The oxidized sodium alginate prepared by the preparation method of the present application has a relatively stable degree of oxidation. The oxidized sodium alginate is used alone or in combination with sodium alginate, which can effectively control the degradation rate of drug-loaded microspheres, tissue engineering scaffolds and in vivo wound dressings in the human body. DETAILED DESCRIPTION

[0023] The present application is further described in detail below with reference to the embodiments.

[0024] Preparation Example 1-4 of Hydrophilic Modified Polytetrafluoroethylene Filter Membrane Preparation Example 1 5 g of polytetrafluoroethylene filter membrane, sodium p-styrene sulfonate, sodium bisulfite and water were mixed, nitrogen was introduced and heated to 60°C, acrylic acid and ammonium persulfate were slowly and continuously added dropwise, and after reacting for 5 hours, the polytetrafluoroethylene filter membrane was taken out, washed and dried to obtain a hydrophilic modified polytetrafluoroethylene filter membrane; wherein the concentration of sodium p-styrene sulfonate was 11wt%, the mass ratio of sodium p-styrene sulfonate to acrylic acid was 6:7.1, the concentration of ammonium persulfate was 1.5wt%, and the concentration of sodium bisulfite was 1wt%.

[0025] Preparation Example 2 5 g of polytetrafluoroethylene filter membrane, sodium p-styrene sulfonate, sodium bisulfite and water were mixed, nitrogen was introduced and heated to 55°C, acrylic acid and ammonium persulfate were slowly and continuously added dropwise, and after reacting for 5.5 hours, the polytetrafluoroethylene filter membrane was taken out, washed and dried to obtain a hydrophilic modified polytetrafluoroethylene filter membrane; wherein the concentration of sodium p-styrene sulfonate was 12wt%, the mass ratio of sodium p-styrene sulfonate to acrylic acid was 6:6.8, the concentration of ammonium persulfate was 1.7wt%, and the concentration of sodium bisulfite was 1.2wt%.

[0026] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that in Preparation Example 3, the mass ratio of sodium p-styrene sulfonate to acrylic acid is 6:5.

[0027] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the mass ratio of sodium p-styrene sulfonate to acrylic acid in Preparation Example 4 is 6:8. Example

[0028] Example 1 A method for preparing oxidized sodium alginate comprises the following steps: Oxidation: Sodium alginate was added into water to prepare an 8wt% sodium alginate solution, sodium periodate solution was added into the sodium alginate solution and mixed evenly, the molar ratio of sodium alginate to sodium periodate was 1:0.03, after reacting at 70°C for 2h, excess ethylene glycol was added to terminate the oxidation reaction; Precipitation: adding excess acetone to the solution after the reaction, centrifugation, dehydration, precipitation, separation, and drying to obtain powder A; Condensation: Powder A and ethylene glycol are mixed evenly at a molar ratio of 1:0.01, and dry HCl gas is introduced. After being kept warm at 14°C for 7 hours, the mixture is extracted with chloroform. After the extract is dried, the chloroform is evaporated to obtain powder B. Filtration: Powder B is dissolved in acetone, and magnetic stirring is performed to form a uniform solution. The uniform solution is filtered 4 times using a filter membrane to obtain a filtrate. The filtrate is subjected to static precipitation, separation, and drying to obtain powder C. In this embodiment, the filter membrane is the hydrophilic modified polytetrafluoroethylene filter membrane prepared in Preparation Example 1; Hydrolysis: After powder C is dissolved in water, phosphoric acid is added to adjust the pH of the solution to 3.5. After reacting for 1 hour, an excess of acetone is added, and static precipitation, separation, and drying are performed. The process of adding acetone, precipitation, separation, and drying is repeated many times to finally obtain oxidized sodium alginate powder.

[0029] Example 2 A method for preparing oxidized sodium alginate comprises the following steps: Oxidation: sodium alginate was added into water to prepare a 10wt% sodium alginate solution, sodium periodate solution was added into the sodium alginate solution and mixed evenly, the molar ratio of sodium alginate to sodium periodate was 1:0.04, after reacting at 50°C for 2.2h, excess ethylene glycol was added to terminate the oxidation reaction; Precipitation: adding excess acetone to the solution after the reaction, centrifugation, dehydration, precipitation, separation, and drying to obtain powder A; Condensation: Powder A and ethylene glycol at a molar ratio of 1:0.02 were mixed evenly, and dry HCl gas was introduced. After being kept warm at 16°C for 6 hours, chloroform was used for extraction. After the extract was dried, the chloroform was evaporated to obtain powder B; Filtration: Powder B is dissolved in acetone, and magnetic stirring is performed to form a uniform solution. The uniform solution is filtered 4 times using a filter membrane to obtain a filtrate. The filtrate is subjected to static precipitation, separation, and drying to obtain powder C. In this embodiment, the filter membrane is the hydrophilic modified polytetrafluoroethylene filter membrane prepared in Preparation Example 2; Hydrolysis: After powder C is dissolved in water, phosphoric acid is added to adjust the solution pH to 4. After reacting for 1.2 hours, excess acetone is added, and static precipitation, separation, and drying are performed. The process of adding acetone, precipitation, separation, and drying is repeated many times to finally obtain oxidized sodium alginate powder.

[0030] Example 3 The difference between Example 3 and Example 1 is that in Example 3, the filter membrane is the hydrophilic modified polytetrafluoroethylene filter membrane prepared in Preparation Example 3.

[0031] Example 4 The difference between Example 4 and Example 1 is that in Example 4, the filter membrane is the hydrophilic modified polytetrafluoroethylene filter membrane prepared in Preparation Example 4.

[0032] Example 5 The difference between Example 5 and Example 1 is that in Example 5, the molar ratio of sodium alginate to sodium periodate is 1:0.001.

[0033] Example 6 The difference between Example 6 and Example 1 is that in Example 6, the molar ratio of sodium alginate to sodium periodate is 1:0.05.

[0034] Example 7 The difference between Example 7 and Example 1 is that in Example 7, the molar ratio of powder A to ethylene glycol is 1:0.001.

[0035] Example 8 The difference between Example 8 and Example 1 is that in Example 8, the molar ratio of powder A to ethylene glycol is 1:0.05.

[0036] Example 9 The difference between Example 9 and Example 1 is that in Example 9, phosphoric acid is added to adjust the pH to 3 during the hydrolysis step.

[0037] Example 10 The difference between Example 10 and Example 1 is that in Example 10, phosphoric acid is added to adjust the pH to 5 during the hydrolysis step.

[0038] Embodiment 11 The difference between Example 11 and Example 1 is that in Example 11, the filter membrane is a polytetrafluoroethylene filter membrane.

[0039] Comparative Example A method for preparing oxidized sodium alginate comprises the following steps: Oxidation: Sodium alginate was added into water to prepare an 8wt% sodium alginate solution, sodium periodate solution was added into the sodium alginate solution and mixed evenly, the molar ratio of sodium alginate to sodium periodate was 1:0.03, after reacting at 70°C for 2h, excess ethylene glycol was added to terminate the oxidation reaction; Precipitation: adding excess acetone to the solution after the reaction, centrifugation dehydration, precipitation, separation, drying, to obtain powder A; Filtration: dissolving powder A in acetone, magnetic stirring to form a uniform solution, using a filter membrane to filter the uniform solution 4 times to obtain a filtrate, the filtrate is subjected to static precipitation, separation, drying, to obtain oxidized sodium alginate powder, in this embodiment, the filter membrane is the hydrophilic modified polytetrafluoroethylene filter membrane prepared in Preparation Example 1.

[0040] Detection Methods 1. Performance test of oxidized sodium alginate Oxidized sodium alginate was prepared according to the preparation method of Examples 1-11. Three groups of oxidized sodium alginate were prepared according to the preparation method of the comparative example, which were recorded as comparative example ①, comparative example ②, and comparative example ③. The iodine titration method was used to detect the oxidation degree of powder A and the oxidized sodium alginate powder. The BCA method was used to detect the protein content in the oxidized sodium alginate powder, and the results were recorded in Table 1.

[0041] Table 1 Test result record Compared with Comparative Examples ①-③, in Example 1-2, the oxidation degree of powder A is similar to that of oxidized sodium alginate, while in Comparative Examples ①-③, the oxidation degree of oxidized sodium alginate is increased compared with the corresponding oxidation degree of powder A in Comparative Examples ① and ③, while that in Comparative Example ② is decreased, and the difference between the oxidation degree of oxidized sodium alginate and the oxidation degree of powder A is large, indicating that during the subsequent purification and precipitation process of powder A in Comparative Examples ①-③, the oxidation degree of oxidized sodium alginate in powder A is affected by environmental factors and the like, and the oxidation degree changes, resulting in a large deviation between the oxidation degree of oxidized sodium alginate and the initial expectation, and the change in the oxidation degree is random and cannot be predicted.

[0042] In Example 1-2, the oxidation degree of oxidized sodium alginate is similar to that of powder A, with a small difference. In Example 1-2, ethylene glycol is used to protect the aldehyde group of oxidized sodium alginate, and the generated acetal is stable in nature and not easy to denature and react. After the acetal is hydrolyzed, the aldehyde group is regenerated, so that the oxidation degree of oxidized sodium alginate is relatively stable and is less affected by various factors in the purification and precipitation processes. The oxidation degree of the finished oxidized sodium alginate is similar to that of powder A, and the oxidation degree of powder A can be regulated by the molar ratio of sodium alginate to sodium periodate, thereby obtaining oxidized sodium alginate with high purity and controllable oxidation degree.

[0043] Compared with Example 1, in Example 3-4, the protein content is improved. When the filter membrane of Example 3-4 is hydrophilically modified, the mass ratio of sodium styrene sulfonate to acrylic acid is changed, indicating that the mass ratio of sodium styrene sulfonate to acrylic acid will affect the modification effect of the polytetrafluoroethylene filter membrane. Sodium styrene sulfonate and acrylic acid are copolymerized to form a hydrophilic copolymer which is deposited on the surface of the polytetrafluoroethylene filter membrane. Sulfonic acid groups are introduced into the surface of the polytetrafluoroethylene filter membrane, which increases the hydrophilicity of the polytetrafluoroethylene filter membrane, thereby improving the adsorption and filtration effect of the hydrophilically modified polytetrafluoroethylene filter membrane on protein. After the mass ratio of sodium styrene sulfonate to acrylic acid is changed, the deposition amount of the copolymer is changed, and the hydrophilic modification effect of the polytetrafluoroethylene filter membrane is also changed, so that in Example 3-4, the filtration effect of the filter membrane on protein is deteriorated and the protein content is increased.

[0044] Compared with Example 1, the oxidation degree of Example 5 is reduced in Example 5, and the oxidation degree of Example 6 is increased. In Example 5-6, the oxidation degree of oxidized sodium alginate is compared with the oxidation degree of powder A, and the change range is smaller than that of Example 1. Example 5-6 changes the molar ratio of sodium alginate to sodium periodate, indicating that the addition amount of sodium periodate directly affects the oxidation degree of oxidized sodium alginate, and the oxidation degree of oxidized sodium alginate can be changed by adjusting the molar ratio of sodium alginate to sodium periodate.

[0045] Compared with Example 1, in Examples 7-8, the degree of oxidation of oxidized sodium alginate is greater than that of powder A in Examples 5-6, while the degree of change in Example 7 is greater, while the degree of change in Example 8 is similar to that in Example 1, and there is no significant change, indicating that the molar ratio of powder A to ethylene glycol will affect the protective effect of ethylene glycol on the aldehyde groups in oxidized sodium alginate. When the amount of ethylene glycol added is low, the aldehyde groups in the oxidized sodium alginate are not fully protected, so that some aldehyde groups are not protected, which is affected in the subsequent filtration and precipitation processes, thereby affecting the degree of oxidation of the oxidized sodium alginate. When the amount of ethylene glycol added is high, the molar ratio of powder A to ethylene glycol selected in this application is an excess of ethylene glycol. Continuing to increase the amount of ethylene glycol added does not significantly enhance the protective effect on the aldehyde groups.

[0046] Compared with Example 1, the oxidation degree of Example 9 in Examples 9-10 changes less, while in Example 10, the oxidation degree of oxidized sodium alginate is lower than that of powder A, indicating that the pH of the solution affects the hydrolysis of acetal. Acetal is hydrolyzed to form aldehydes and alcohols under acidic conditions, and the hydrolysis rate is related to the pH of the solution. As the pH decreases, the hydrolysis rate increases. In Example 10, the increase in pH results in a lower hydrolysis rate. Under the same time, the acetal is not completely hydrolyzed, so that some aldehyde groups cannot be deprotected, thereby reducing the oxidation degree of Example 10.

[0047] Compared with Example 1, the protein content of Example 11 is improved. The filter membrane of Example 11 is a polytetrafluoroethylene filter membrane. The polytetrafluoroethylene filter membrane that has not been hydrophilically modified has a high hydrophobicity when filtering protein, and the adsorption and filtration effects on proteins are weakened, and the anti-fouling performance is reduced. When the filter membrane is used for multiple filtrations, the polytetrafluoroethylene filter membrane is blocked by impurities and the filtration effect becomes poor, thereby increasing the protein content in Example 11.

[0048] 2. Application test of oxidized sodium alginate According to the preparation method of Example 1-2, oxidized sodium alginate with an oxidation degree of 3% and 5% was prepared respectively, and a PBS solution with a pH of 7.4 was used as a simulated body fluid to simulate physiological conditions at 37°C. The degradation rates of oxidized sodium alginate with an oxidation degree of 5%, oxidized sodium alginate with an oxidation degree of 3%, and a mixture of oxidized sodium alginate with an oxidation degree of 5% and sodium alginate in a ratio of 1:1-3 were detected. The results are as follows: Oxidized sodium alginate with an oxidation degree of 5% degraded in simulated body fluid in 1 week; Oxidized sodium alginate with an oxidation degree of 3% degraded in simulated body fluid in 2.5 weeks; Oxidized sodium alginate with an oxidation degree of 5% was mixed with sodium alginate in a 1:1 ratio and degraded in simulated body fluids in 1 month; Oxidized sodium alginate with an oxidation degree of 5% was mixed with sodium alginate in a ratio of 1:3 and degraded in simulated body fluids within 3 months.

[0049] The above results can show that the degradation rate of oxidized sodium alginate is faster in the in vivo environment, which is more in line with the conditions of use of drug-loaded microspheres, tissue engineering scaffolds, and in vivo wound dressings, etc., which are applied to the human body. The degradation rate can be regulated by the oxidation degree of oxidized sodium alginate and the compound ratio of oxidized sodium alginate to sodium alginate, so that the prepared drug-loaded microspheres, tissue engineering scaffolds, and in vivo wound dressings, etc., not only maintain the mechanical strength they should have during their action, but also can be naturally degraded in the human body after taking effect, without affecting the recovery of the human body. The oxidized sodium alginate prepared by the preparation method provided in this application can meet the requirements for the specific oxidation degree of oxidized sodium alginate in this application.

[0050] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A method for preparing oxidized sodium alginate, characterized in that: The following steps are involved: Oxidation: Add sodium alginate into water to prepare sodium alginate solution, add sodium periodate solution into the sodium alginate solution and mix well, react at 50-70°C for 2-2.2h, then add excess ethylene glycol to terminate the oxidation reaction; Precipitation: adding excess acetone to the solution after the reaction, centrifugation, dehydration, precipitation, separation, and drying to obtain powder A; Condensation: Powder A and ethylene glycol are mixed evenly, and dry HCl gas is introduced. After keeping warm at 14-16°C for 6-7 hours, chloroform is used for extraction. After the extract is dried, the chloroform is evaporated to obtain powder B; Filtration: Powder B is dissolved in acetone, and magnetic stirring is performed to form a uniform solution. The uniform solution is filtered multiple times using a filter membrane to obtain a filtrate. The filtrate is subjected to static precipitation, separation, and drying to obtain powder C; Hydrolysis: After powder C is dissolved in water, phosphoric acid is added to adjust the pH. After reacting for 1-1.2 hours, excess acetone is added, and static precipitation, separation, and drying are performed. The process of adding acetone, precipitation, separation, and drying is repeated many times to finally obtain oxidized sodium alginate powder.

2. The method for preparing oxidized sodium alginate according to claim 1, characterized in that: In the sodium alginate solution, the concentration of sodium alginate is 8-10wt%, and the molar ratio of sodium alginate to sodium periodate is 1:0.03-0.

04.

3. The method for preparing oxidized sodium alginate according to claim 1, characterized in that: The molar ratio of the powder A to ethylene glycol is 1:0.01-0.

02.

4. The method for preparing oxidized sodium alginate according to claim 1, characterized in that: In the hydrolysis step, phosphoric acid is added to adjust the pH to 3.5-4.

5. The method for preparing oxidized sodium alginate according to claim 1, characterized in that: The filter membrane is a hydrophilic modified polytetrafluoroethylene filter membrane.

6. The method for preparing oxidized sodium alginate according to claim 5, characterized in that: The preparation method of the hydrophilic modified polytetrafluoroethylene filter membrane comprises the following steps: after mixing the polytetrafluoroethylene filter membrane, sodium p-styrene sulfonate, sodium bisulfite and water, heating to 55-60° C. after introducing nitrogen, slowly and continuously dripping acrylic acid and ammonium persulfate (1.5%), reacting for 5-5.5 hours, taking out the polytetrafluoroethylene filter membrane, washing and drying, and obtaining the hydrophilic modified polytetrafluoroethylene filter membrane.

7. The method for preparing oxidized sodium alginate according to claim 6, characterized in that: The mass ratio of sodium p-styrene sulfonate to acrylic acid is 6:(6.8-7.1), and the concentration of sodium p-styrene sulfonate is 11-12wt%.

8. The use of oxidized sodium alginate obtained by the method for preparing oxidized sodium alginate according to any one of claims 1 to 7, characterized in that: Oxidized sodium alginate is used alone or in combination with sodium alginate for drug-loaded microspheres, tissue engineering scaffolds, and in vivo wound dressings.

Citation Information

Patent Citations

  • Modified sodium alginate as well as preparation method and application thereof

    CN116970100A

  • Bio-ink and preparation method and application thereof

    CN118490881A

  • Tissue engineering using injectable, oxidized alginate hydrogels

    WO2013025763A2